Little Bear's friend - Minarik, Else Holmelund; Sendak, Maurice; Ethel and Ira Levine Maurice Sendak Collection (Library of Congress) (New York : Harper & Brothers, publishers, 1960)
One summer Little Bear makes friends with Emily and her doll Lucy.
LC copy stamped: ABP, Gift, Publisher.
Keywords: Bears -- Juvenile fiction; Juvenile literature -- 1960.